The Effect of Salary and Benefits on the Work Spirit of Nurses in PKU Muhammadyah Islamic Hospital Palangka Raya, Central Kalimantan - Yane Puspito Sari (East Asian Journal of Multidisciplinary Research, 2022)
Islamic Hospital PKU Muhamadiyah Palangkaraya has duty and responsibility to increase health service to people in Central Kalimantan. The purpose of this study is to find out the effect of compensation toward the work courage of employees at Islamic Hospital PKU Muhamadiyah Palangkaraya. The data that were collected in this study consist of: a) data about Hospital PKU Muhamadiyah Palangkaraya, b) data about compensation at Hospital PKU Muhamadiyah Palangkaraya. The techniques that were used in collecting the data were observation, interview, documentation and study literature. In this study, the writer conducted questionnaires to nurses of Hospital PKU Muhamadiyah Palangkaraya; 59 questionnaire sheets were conducted and returned to the writer were only 45 questionnaire sheets. In spite of that, the total of respondents was 45. The result of the study is; based on the result of correlation operation, it is known that R2= 0,1, it means that 1% of work courage variable (Y) is mutually influenced by salary and incentive, and other variables, such as leadership and motivation were not analyzed.